EFEKTIVITAS VARIASI PERANGKAP LALAT DI PASAR ANGSO DUO KOTA JAMBI - Susy Ariyani; Supriadi Supriadi; Suhermanto Suhermanto (Poltekkes Kemenkes Jambi, 2022)
Background: The market as a means for the existence of flies can be used as a general indicator based on the existing requirements for good and bad sanitation in a place. The purpose of this study was to determine the Effectiveness of Variation of Fly Traps in the Angso Duo Market, Jambi City. The research location is in the Angso Duo Market, Jambi City. Method: This research method is quasi-experimental with a post test only design with control group with the Anova statistical test approach. Research Results The number of flies trapped with fly traps with bait as fly control in 3 stalls selling dry ingredients at the Angso Duo Market, Jambi City. Results: the difference in the number of flies trapped with fly traps compared to fly glue traps at Angso Duo Market, Jambi City (p-value = 0.0001). Anova F value = 2.268 with a p-value of 0.002 (p > 0.05. Conclusion: there was significant differences in the number of flies from the four trap variations.